Poster 132: Long Term Outcomes of Distal Biceps Injuries: A Comparative Study of Surgical and Non-operative Management at a Mean Follow Up of 13 years. Issue 7 (30th July 2022) - Till, Sara; Song, Bryant; Wilbur, Ryan; Reinholz, Anna; Sanchez-Sotelo, Joaquin; Barlow, Jonathan; Camp, Christopher; Tagliero, Adam
Objectives: Distal biceps tendon tears, although rare, significantly impair patient's elbow mobility and function. There is a paucity of contemporary literature reporting long term outcomes of distal biceps (DB) injuries. Therefore, the authors sought to identify magnetic resonance imaging (MRI) confirmed distal bicep tears and report on (1) patient demographics and injury characteristics of all patients with distal bicep pathology, (2) outcomes of all patients with non-operatively managed DB pathology, and (3) outcomes of all patients with operatively managed DB pathology. Methods: Patients with an MRI-confirmed distal biceps rupture from 1996 to 2016 were identified through an institutional image database. Patients from the initial search were then cross-referenced with the [REDACTED] 1 to ensure record availability. Patients were included if they had complete medical records and ≥5 years of clinical follow-up. Patients with inflammatory arthritis and enthesitis, polytrauma, or incidental findings without clinical assessment were excluded. Medical records were reviewed to confirm the diagnosis of distal biceps tears and obtain further subject details. Results: A total of 158 patients (22 female, 136 male) with a mean age 51.5 years (44.8-61.2) were identified and included. Baseline patient demographics including BMI, smoking status, dominant-handedness, laborer occupation, and gender were gathered (Table 1 ). Patients had a mean clinical follow-up of almost 14 years (Table 1, range 8.4 -17.8). Outcomes of the 52 non-operative and 106 operatively managed patients, included severe complications, functional outcomes, and health-related productivity loss are reported in Table 2. There were 7 re-operations (4%), 5 re-ruptures (3%), and overall 35% of the operatively treated cohort experienced a complication. Conclusions: Patients with distal bicep pathology tended to be a male laborer in their 50s without clinically significantly associated risk factors. The majority of patients regained full ROM, and 83% were able to return to work without modifications, irregardless of operative or non-operative management. At long term follow up, patients treated operatively were more likely to report missing time from work and averaged more days missed than their non-operatively treated counterparts. Additionally, operative patients had no statistically significant gains functional outcomes, and were subject to potential post-operative complications. Surgeon bias may play a role in deciding treatment for distal biceps tears. As such, careful patient selection for surgical intervention for distal biceps pathology should be employed; surgeons should consider restricting surgical intervention to patients who have significant clinical symptoms or fail non-operative management. Table 1. Patient Demographics and Clinical Characteristics Table 2. Outcomes for Operative and Non-Operative Patients.